E agora José? Ideologias de gênero e autores de violência sexual contra crianças e adolescentes - Freitas, Solange Bassetto [UNESP] (2015)
This study aimed to verify the gender ideologies present in the representations of the perpetrators of sexual violence against children and adolescents and their relationship with the committed violence. The data collection was performed by analyzing the transcripts of care provided by re-proposing Project, the authors of such violence, who were inmates between 2006 and 2008. Data analysis allowed us to verify that gender ideologies are made present in the representations of the authors and are used as justification for violence committed when admitted by the subjects. In this sense, it is necessary to overcome or reduce the number of cases of sexual violence against children and adolescents, the redefinition of gender ideologies present in the representations of these authors aspect to be contemplated in the care aspect. Therefore we also consider the need for an educational process that can contribute in the transformation of gender relations, as gender ideologies are part of a socio-historical and cultural context that is only likely to overcome through education